2011
DOI: 10.1016/j.ympev.2011.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogenetic relationships and phenotypic diversity in miniaturized toadlets, genus Brachycephalus (Amphibia: Anura: Brachycephalidae)

Abstract: Toadlets of the genus Brachycephalus are endemic to the Atlantic rainforests of southeastern and southern Brazil. The 14 species currently described have snout-vent lengths less than 18 mm and are thought to have evolved through miniaturization: an evolutionary process leading to an extremely small adult body size. Here, we present the first comprehensive phylogenetic analysis for Brachycephalus, using a multilocus approach based on two nuclear (Rag-1 and Tyr) and three mitochondrial (Cyt b, 12S, and 16S rRNA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 56 publications
5
44
0
Order By: Relevance
“…More generally, there is a lack of information about the relationship between morphological and genetic variability at the intra-specific level. Indeed, due to the very low number of studies investigating the relationship between wing morphology and genetic variability at the intra-specific level for insects, the establishment of a general pattern seems hardly possible [6264]. Among them, [63] have found that higher genetic variability implies higher wing shape variability in populations of butterfly but on the other hand, [64] do not find any concordance.…”
Section: Discussionmentioning
confidence: 99%
“…More generally, there is a lack of information about the relationship between morphological and genetic variability at the intra-specific level. Indeed, due to the very low number of studies investigating the relationship between wing morphology and genetic variability at the intra-specific level for insects, the establishment of a general pattern seems hardly possible [6264]. Among them, [63] have found that higher genetic variability implies higher wing shape variability in populations of butterfly but on the other hand, [64] do not find any concordance.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic relationships within Euparkerella are better supported in the tree inferred using the multilocus concatenated dataset when compared either to the mtDNA tree or the multilocus species tree, as observed in several other case studies [30,6467]. This is likely explained by differences in the sensitivity of distinct methods to gene tree incongruences.…”
Section: Discussionmentioning
confidence: 57%
“…The six genetic units uncovered within Euparkerella from Rio de Janeiro State correspond to populations that are between 15 and 100 km away from the closest congeneric populations. Diversification in relatively small geographic scales seems relatively common in small-bodied, and particularly in miniaturized vertebrates [25,27,30,75,76]. Organismal body size has several functional, ecological, and evolutionary implications, in particular reducing physiological tolerance (e.g., higher sensitivity to dehydration) and dispersal in the case of extremely small-bodied species [27,77].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most species in the genus are aposematically coloured, predominantly in bright yellow or orange hues (Clemente-Carvalho et al 2011). Currently, the genus Brachycephalus encompasses 18 species, all endemic to the Atlantic Rainforest of southern and southeastern Brazil (Pombal and Izecksohn 2011).…”
mentioning
confidence: 99%